The impact of expert- and peer feedback on communication skills of undergraduate dental students – a single-blinded, randomized, controlled clinical trial. Issue 12 (December 2017) - Krause, Felix; Schmalz, Gerhard; Haak, Rainer; Rockenbauch, Katrin
Highlights: Feedback interventions improve communication skills of dental students. Experience of the feedback provider has no impact on the outcome of interventions. Peer-feedback interventions should be embedded in the curricular dental courses. Abstract: Objective: To evaluate the effect of peer- and expert feedback on communication skills of undergraduate dental students. Methods: All students of the first clinical treatment course (n = 46) were randomly assigned into two groups. For three times a medical-dental interview/consultation of each student with a real patient was videotaped. After every consultation the videos were assessed either by a person experienced in communication (expert group) or by a fellow student (peer group), giving the students feedback regarding their chairside performed communication skills. Before and after the feedback-interventions all students conducted an interview with simulated patients, which was rated using a validated global rating and analyzed statistically. Results: Global ratings mean scores after feedback-intervention were significantly improved (p < 0.05). Thereby, no significant differences in the overall assessment could be observed between expert and peer feedback (p > 0.05). Conclusion: During this study students improved their communication skills in dentist-patient interactions. The communication experience of the feedback provider seems not to have any impact on the communication skills in undergraduate dental students. Practice implications: The clinical courses in dentistry offer the opportunity to implement peer-feedback interventions in real treatment situation as part of communication training to longitudinally improve communication skills.